Phosphorus fractionation in soils of the Paraguayan Chaco under pristine and anthropogenic conditions - Candia-Díaz, Ana Beatriz; Rasche-Álvarez, Jimmy Walter; Escobar Decoud, Natalia Carolina; Fatecha Fois, Diego Augusto; Corrales-Brenes, Eduardo (2025)
Land use changes profoundly impact the natural dynamics of soil phosphorus (P), potentially leading to decreased P concentrations. This study aimed to evaluate the different P fractions in soils from Paraguay Central Chaco under pristine and anthropogenic conditions. A randomized complete block design was utilized with two treatments (pristine and anthropogenic usage). Thirty-four composite soil samples were collected from the region at the layer of 0.00-0.20 m, followed by chemical fractionation of P into labile, moderately labile, and non-labile categories, further classified into inorganic and organic types. Collected data were analyzed using general and mixed linear models. Significant differences (p<0.05) were explored using Fisher’s least significant difference test for mean comparisons. Pristine soils consistently exhibited higher P levels across most evaluated fractions (labile, moderately labile, non-labile, and inorganic) compared to those affected by anthropogenic activities. Organic P fraction showed no significant differences. These findings highlight that converting pristine areas to agricultural use reduces soil P levels, posing significant implications for environmental management and agricultural productivity.